The impact of meropenem shortage and post-prescription review and feedback on broad-spectrum antimicrobial use: An interrupted time-series analysis - Kohei Maruyama; Kiyoshi Sekiya; Noriyuki Yanagida; Shuhei Yasuda; Daisuke Fukumoto; Satoshi Hosoya; Hiromitsu Moriya; Motoko Kawabe; Tatsuya Mori (Elsevier, 2024)
Summary: Background: Meropenem (MEPM) holds significance in treating severe infections and drug-resistant bacteria. There are concerns that antimicrobial shortages may lead to the use of alternative antimicrobials that are less effective and safer. We have responded to the MEPM shortage with post-prescription monitoring and feedback (PPRF) with no restrictions on MEPM initiation. We aimed to assess the impact of the MEPM shortage and the PPRF on broad-spectrum antimicrobial use and mortality. Methods: This retrospective study was conducted in a single hospital in Japan. The period from October 2021 to August 2022 was defined as the period before the MEPM shortage, and the period from September 2022 to March 2023 was defined as the period during the MEPM shortage. To support the appropriate use of antimicrobials during MEPM shortages, the antimicrobial stewardship team (AST) developed a list of alternatives to MEPM. An interrupted time series analysis was used to assess changes in use and mortality among patients receiving broad-spectrum antimicrobials over the study period. Discussion: The shortage of MEPM and PPRF temporarily increased the use of alternative cefepime; however, the subsequent change in days of therapy and days of coverage of broad-spectrum antimicrobials suggests a decrease in the use of these antimicrobials. Despite these shifts, the mortality rates remained stable, suggesting that the response to the shortage did not adversely affect treatment outcomes. Conclusion: In the context of antimicrobial shortages, AST support plays an important role in enabling physicians to make optimal use of antimicrobials.